Social network of teachers of academic discipline - G. I. Skorokhod (Academy of Cognitive and Natural Sciences, 2013)
Cloud technology creates fundamentally different opportunities for both communication and collaboration on a single product. Such a product in pedagogical activity can be a course of an academic discipline. Each course separately should contribute to the achievement of the dual purpose of higher education: 1) preparation for entry into the profession, 2) formation and development of the personality, its general, mental and moral development. In order to achieve this twofold goal, preparation for professional work must be conducted in such a way as to promote personal development. Moreover, it can be argued that in today's situation, when many university graduates do not work in their specialty and do not intend to do so, the task of general personal development comes to the fore.